Towards a Reconceptualization of Social Policy: A Review of the Recent Theoretical Debate - Arias Ramírez, Rafael (2008)
The formulation of social policy in Latin America in the 80's was influenced in an adverse economic context due not only to the effects of the international crisis of those years but also because of the strong confrontation by many upon the prevailing policies of economic development (Structuralism), as well as by the prevalence then reached.